Host-parasite transcriptomics during immunostimulant-enhanced rejection of salmon lice (Lepeophtheirus salmonis) by Atlantic salmon (Salmo salar) - Ben J.G. Sutherland; Jennifer M. Covello; Sarah E. Friend; Jordan D. Poley; Kim W. Koczka; Sara L. Purcell; Tara L. MacLeod; Bridget R. Donovan; Jorge Pino; Jose Luis González-Vecino; Javier Gonzalez; Jose Troncoso; et al. (Canadian Science Publishing, 2017)
Salmon lice (Lepeophtheirus salmonis) are important ectoparasites of wild and farmed salmonids and cause major losses to the salmon farming industry throughout the Northern Hemisphere. With the emergence of resistance to several commonly used parasiticides, novel control strategies and integration of multiple treatment options are needed, including host immunostimulation. Here, we investigate the effects of a functional feed containing a peptidoglycan and nucleotide formulation on L. salmonis infection of Atlantic salmon (Salmo salar) by characterizing lice infection levels, the expression of several host immune genes, and the parasite transcriptomic response to the immunostimulated host. Although initial infection intensities were low, the low dose (LD) immunostimulant diet reduced the total lice burden by 50% relative to controls. Immunostimulant fed hosts up-regulated interleukin-1β in the skin and spleen. This gene has been implicated in successful responses of several salmonid species to salmon lice but is typically not observed in Atlantic salmon, suggesting a favorable influence on the immune response. Lice infecting LD immunostimulated salmon overexpressed genes putatively involved in parasite immunity, including carboxylesterases, and underexpressed genes putatively involved in feeding (e.g., proteases). These lice response genes further improve the characterization of the transcriptome of the non-model parasite by identifying genes potentially involved in evading host immunity.